Do certain rituals adapt to psychology or does psychology adapt to rites? Post mortem photography: the last “picture of life” in “death” - Iorio, Silvia; Gazzaniga, Valentina; Ciliberti, Rosagemma; Licata, Marta (Acta Biomedica Atenei Parmensis, 2020)
In death and mourning, why should we think that rites adapt to psychology and not vice-versa? Or believe that psychological workings grow into a rite or ritual? When analysing practices related to rites of passage, death emerges as a rupture – or breakage – of social status.